2018
DOI: 10.1259/bjr.20180458
|View full text |Cite
|
Sign up to set email alerts
|

A UK survey exploring the assistant practitioner role across diagnostic imaging: current practice, relationships and challenges to progression

Abstract: Skill mix implementation is inconsistent across modalities and geography in the UK. Opportunities for further workforce utilisation and expansion are evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…35 In an extrapolation analysis that assumed a 4% annual growth rate for the RW across the UK, it is suggested that there are approximately 34,241 radiographers [diagnostic ( n = 29,248) and therapeutic ( n = 4,993)] currently registered in the UK. Snaith and colleagues 36 previously reported the contributions of APs in easing staff shortages and facilitation of efficient service delivery. The Society and College of Radiographers (SCoR) states there are 189 voluntarily accredited APs across diagnostic and therapeutic radiography practice on their register in June, 2020 (personal communication, M Landau).…”
Section: Methodsmentioning
confidence: 99%
“…35 In an extrapolation analysis that assumed a 4% annual growth rate for the RW across the UK, it is suggested that there are approximately 34,241 radiographers [diagnostic ( n = 29,248) and therapeutic ( n = 4,993)] currently registered in the UK. Snaith and colleagues 36 previously reported the contributions of APs in easing staff shortages and facilitation of efficient service delivery. The Society and College of Radiographers (SCoR) states there are 189 voluntarily accredited APs across diagnostic and therapeutic radiography practice on their register in June, 2020 (personal communication, M Landau).…”
Section: Methodsmentioning
confidence: 99%
“…the four-tier system 18 . Although multidisciplinary practice is a feature to an extent in all clinical environments, it was particularly apparent within breast clinics given the wide range of staff involved in the patient pathway 19,20 .Specifically, the included studies referred to breast care nurse specialists, pathologists, advanced nurse practitioners, advanced mammography practitioners, consultant radiographers, consultant radiologists, consultant breast surgeons and assistant practitioners as all being essential in the patient pathway 18,21,22,23 .…”
Section: Included Studiesmentioning
confidence: 99%
“…One way in which multidisciplinary practice allowed time for training and development was to more effectively allocate workloads. Rees in 2014 24 Snaith and colleagues in 2018 21 and Deane and colleagues in 2019 25 Although all the studies suggested that multidisciplinary practice in itself, particularly in breast imaging, works well, the literature also identified a number of contextual factors which inhibited multidisciplinary practice and therefore advanced practice in breast clinics. For example, McLoughlin and colleagues in 2014 22 found that for advanced practice to flourish there must be a sufficient number of staff to continue providing the more 'traditional' and 'routine' care.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This might also explain the growth in assistant practitioners working with increasing independence and autonomy within projection radiography (and mammography as a subset of this). 3 As a result, with the exception of mammography which has become a specialist area of practice within the context of breast imaging, general projection radiography has been apparently demoted as an area of practice not worthy of specialization or higher level learning and nowhere is this more evident than within career advancement choices and pre-and post-registration education programmes.…”
mentioning
confidence: 99%